3D acoustic metamaterial-based mechanical metalattice structures for low-frequency and broadband vibration attenuation. (15th May 2020) - An, Xiyue; Lai, Changliang; Fan, Hualin; Zhang, Chuanzeng
Abstract: In this paper, a new type of three-dimensional (3D) truss-lattice structures for low-frequency and broadband elastic wave absorption is proposed. The local resonance mechanism used in acoustic/elastic metamaterials (AMs) for generating low-frequency bandgaps, in which elastic waves cannot pass through, is introduced into the continuous body-centered cubic lattice structures by only making the cross-struts in each unit-cell have a radius jump discontinuity. This method is easy to realize for practical engineering compared with the conventional acoustic metamaterials usually made of different materials. The band structures of the 3D AM-based lattice structures are calculated and the edge modes of each bandgap are analyzed to understand the effects of each component of the unit-cell on the bandgap formation. The effects of the structural and material parameters on the bandgaps are investigated and two kinds of composite AM-based lattice structures are suggested for broadening the bandgap width based on the parametric study. As the design is based on increasing the radii of some parts of the cross-struts inside the unit-cell, the mechanical properties are enhanced. The limiting conditions of the static properties of the 3D AM-based lattice structures for broadening the bandgaps are illustrated. Finally, experiments were carried out to validate the results. This design strategy provides new possibilities for the development of lattice truss structures with both bearing and vibration reduction requirements.